1995
DOI: 10.7863/jum.1995.14.11.805
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal vein compression due to popliteal artery aneurysm: effects of aneurysm size.

Abstract: Unlike the venous compression associated with larger popliteal artery aneurysms, which frequently is associated with deep vein thrombosis, the venous compression caused by the moderate sized (greater than 2 cm and less than 3 cm) aneurysms in the reported cases is not associated with thrombosis. The extrinsic compressive effect of these moderate sized popliteal artery aneurysms on the adjacent vein is shown to vary with the patient's leg position. Three of the four patients with unilateral leg swelling discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…This is similar to another study, where 4 patients with PAA between 2 cm and 3 cm were presented with venous extrinsic compression. 4 Our patient’s PAAs were larger than these sizes; hence, causing signs and symptoms similar to the aforementioned studies. Mahmood et al 10 , on their study of 41 patients with 52 PAAs, reported only one patient with extrinsic venous compression by the mass effect of the PAA, causing leg swelling.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is similar to another study, where 4 patients with PAA between 2 cm and 3 cm were presented with venous extrinsic compression. 4 Our patient’s PAAs were larger than these sizes; hence, causing signs and symptoms similar to the aforementioned studies. Mahmood et al 10 , on their study of 41 patients with 52 PAAs, reported only one patient with extrinsic venous compression by the mass effect of the PAA, causing leg swelling.…”
Section: Discussionsupporting
confidence: 79%
“…Once a PAA reach a size greater than 4 cm, the compressive effect on the popliteal vein has a higher probability of being associated with DVT. 4 Our patient did not present this complication, even though his aneurysms measured more than 4 cm.…”
Section: Discussionmentioning
confidence: 47%
“…Although the origins of the CAD are unknown, adventitial cysts are both biochemically and histologically similar to the ganglion. There are also vascular complications (e.g., popliteal aneurysm as described by Kotval et al) 3 Another vascular complication is popliteal entrapment, which was described by T. P. Anderson Stuart in 1879 as a variant of the popliteal artery. This is an uncommon condition usually affecting young otherwise healthy athletic men who are pain free at rest but have aching and numbness develop in the foot after exercise.…”
Section: Discussionmentioning
confidence: 98%
“…Popliteal artery aneurysms large enough to impinge on the popliteal vein may result in the development of DVT. 18 Popliteal reflux with turbulent flow in the popliteal vein associated with a small ID is also correlated with a higher incidence of DVT. 19 Popliteal vein compression syndrome in obese patients is associated with a high rate of DVT 11 and, in the non-obese population, chronic popliteal vein entrapment caused by abnormal origin of the medial head of gastrocnemius or thick perivenous fascia is associated with symptoms such as swelling and pain of the lower limb.…”
Section: Discussionmentioning
confidence: 99%